Characteristics Of Those Who Dominated And Those Who Were Dominated From Historical Verses In al-Quran: Lessons Learnt Analysis - Mansor, Sulaiman (University of Malaya, 2013)
The article discusses about those who dominated and those who were dominated based on the explanation of related historical verses in alQuran. The aim of the discussion is to gain lessons from them, specifically in embracing the challenges where Muslims are facing which are the clashes with other party such as those in the western regions and their allies. By the end of the article, it will elucidate the question regarding the losing of power which was in Muslims’ grasp and at the same time present a relevant guideline on the ways Muslims can restore their power.